Зміна кінематики зубофрезерного верстата для нарізання зубчастих коліс радіально-коловим способом - Громнюк, С. І.; Грицай, І. Є. (НТУ "ХПІ", 2015)
В статті розглянуто напрямки модернізації серійних зубофрезерних верстатів з ручним керуванням для забезпечення нарізання зубчастих коліс дисковою фрезою в умовах неперервного обкочування за радіально-коловим способом. Кінематика верстата після її зміни передбачає програмне керування приводами основного руху і зворотно-поступального періодичного переміщення інструментальної каретки з зубцевою частотою та дає змогу нарізати зубчасті колеса з будь-яким профілем зубчастого вінця.

The article viewed directions upgrading serial gear manually controlled gear’s cutter machine under for radial- circular way. Changing gear kinematics conventional machine is as follows. Rotating disk mill provided by servomotor controlled controller or computer. Speed cutters of the mill take depending on mechanical properties of the cog-wheel’s material and its diameter. Periodic mill’s motion in the radial direction has a frequency equal to the number of teeth and wheels by means of servomotor. Instrumental carriage with a cutter installed on ball bearings in double guides. Manage servomotor carriage is also carried out by the controller or computer. Set value displacement, depending on the module. Simultaneous control of two working movements – cutting speed and radial displacement cutters cut serrated surfaces allows any profiles- involute, sinusoidal, Novikov gearing, arch, asymmetrical, stars and others.
Changing the kinematics of gear hobbing machine for gear cutting by radial-circular method
Keywords: зубчасті передачі; програмований привід; серводвигун; мехатроніка; ефективність процесів нарізання; gear cutter machine; radial-circular way; CNC-cutting; effectiveness